Kajian Teknis & Keekonomian Pembangkit Listrik Tenaga Biomasa Sawit; Kasus: Di Pabrik Kelapa Sawit Pinang Tinggi, Sei Bahar, Jambi - Febijanto, Irhan (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2011)
Utilization of empty fruit bunch (EFB) waste as a fuel for power electric generation is one of the options available for palm oil factory in the effort to reduce EFB waste. At the moment, there are several options to utilize EFB waste such as fertilization and composting. However, both ways show ineffective result, particularly in handling huge amount of EFB. Up to now, Indonesia only has a limited number of EFB fueled power plants. This paper explains technically and economically EFB fueled power plant supplying to PLN grid in Pinang Tinggi Palm Oil Factory located at Sei Bahar, Jambi Province. The economical feasibility is low, if the additional revenue generated from selling remnant oil, selling ash of EFB and selling credit carbon are not counted as an income. Using these additional revenues, the IRR project increased from 2.03% to 15.12%. The investment cost and the selling electricity price are critical sensitivity factors for project economics.Â